2023
DOI: 10.3389/fimmu.2023.1114321
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck dermatitis is exacerbated by Malassezia furfur colonization, skin barrier disruption, and immune dysregulation

Abstract: Introduction & objectivesHead and neck dermatitis (HND) is a refractory phenotype of atopic dermatitis (AD) and can be a therapeutic challenge due to lack of responsiveness to conventional treatments. Previous studies have suggested that the microbiome and fungiome may play a role in inducing HND, but the underlying pathogenic mechanisms remain unknown. This study aimed to determine the link between HND and fungiome and to examine the contribution of Malassezia furfur.Materials and methodsTo identify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…33 Malassezia disrupts the barrier of the stratum corneum, allowing the permeation of various allergens and sensitization to them. 34 AD patients with occurrence of HZ during upadacitinib treatment had higher baseline LDH values compared to those without.…”
Section: Ta B L E 6 (Continued)mentioning
confidence: 79%
See 2 more Smart Citations
“…33 Malassezia disrupts the barrier of the stratum corneum, allowing the permeation of various allergens and sensitization to them. 34 AD patients with occurrence of HZ during upadacitinib treatment had higher baseline LDH values compared to those without.…”
Section: Ta B L E 6 (Continued)mentioning
confidence: 79%
“…Malassezia colonizes the face and contributes to the development of head and neck rash in patients with AD 33 . Malassezia disrupts the barrier of the stratum corneum, allowing the permeation of various allergens and sensitization to them 34 . A previous study reported that AD patients with head and neck rash had elevated levels not only of Malassezia ‐specific IgE, but of total IgE 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, Malassezia furfur abundantly colonized on head and neck may contribute to the pathogenesis of treatment‐resistant erythema in AD patients 27 . M. furfur may disrupt the barrier of stratum corneum by reducing the esterified omega‐hydroxyacyl‐sphingosine content and inducing the expression of VEGF, IL‐31, and IL‐33 in epidermal keratinocytes and of VEGF receptor, TNF‐α, and IL‐1β in dermal endothelial cells, which may promote inflammation and angiogenesis, leading to the generation of treatment‐resistant erythema 28 …”
Section: Discussionmentioning
confidence: 99%
“…27 M. furfur may disrupt the barrier of stratum corneum by reducing the esterified omega-hydroxyacyl-sphingosine content and inducing the expression of VEGF, IL-31, and IL-33 in epidermal keratinocytes and of VEGF receptor, TNFα, and IL-1β in dermal endothelial cells, which may promote inflammation and angiogenesis, leading to the generation of treatment-resistant erythema. 28 This study has some limitations. First, the sample size is small.…”
mentioning
confidence: 91%